The Possibility and Necessity of the Human-Centered AI in Legal Theory and Practice - A. V. Rezaev; N. D. Tregubova (Journal of Digital Technologies and Law, 2023)
Objective: the paper aims to define the problems juridical theory and practice face with the progress of AI technologies in everyday life and correlate these problems with the human-centered approach to exploring artificial intelligence (Human-Centered AI).Methods: the research  critically analyzes  the relevant literature from various disciplines: jurisprudence, sociology, philosophy, and computer sciences.Results: the article articulates the prospects and problems the legal system confronts with the advancement of digital technologies in general and the tools of AI specifically. The identified problems are correlated with the provisions of the human-centered approach to AI. The authors acknowledge the necessity for AI inventors, as well as the owners of companies participating in the race to develop artificial intelligence technologies, to place humans, not machines, into the focus of attention as a primary value. In particular, special effort should be directed towards collecting and analyzing high-quality data for the organization of artificial intelligence tools development, taking into account that nowadays, the tools of AI are as practical as the data on which they are trained are effective.The authors formulate three principles of human-centered AI for the legal sphere: 1) a human as a necessary link in the chain of making and executing legal decisions; 2) the need to regulate artificial intelligence at the international law level; 3) formulating “a taboo” for introducing the artificial intelligence technologies.Scientific novelty: the article manifests one of the first attempts in the Russianlanguage scientific literature to outline the prospects of developing humancentered AI methodology in jurisprudence. Based on an analysis of special literature, the authors formulate three principles of including artificial intelligence into juridical theory and practice according to the assumptions of a human-centered approach to AI.Practical significance: the principles and arguments the article advances can be helpful in the legal regulation of artificial intelligence technologies and their harmonious inclusion into legal practices.